2005
DOI: 10.1007/s11095-005-6137-z
|View full text |Cite
|
Sign up to set email alerts
|

Region-Dependent Role of the Mucous/Glycocalyx Layers in Insulin Permeation Across Rat Small Intestinal Membrane

Abstract: The regional difference in the contribution of the mucous/glycocalyx layers in rat small intestine, as a diffusional or enzymatic barrier, to the absorption of insulin was investigated by in vitro studies. The mucous/glycocalyx layers from the duodenum, the jejunum, and the ileum in rat were successfully removed without damaging membrane integrity, by exposing them to a hyaluronidase solution in situ. In an in vitro transport experiment, the apparent permeability coefficient (P(app)) of insulin for the hyaluro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…The mucus/glycocalyx layers presumably also provide an enzymatic barrier and/or diffusional barrier. The enzymatic degradation of insulin in the mucus/glycocalyx layers tends to increase toward the upper small intestine in the following order: duodenum>jejunum>ileum (38). By contrast, the colonic coadministration of insulin and penetratin had a smaller effect on increasing insulin absorption, even though the proteolytic activity in the colon may be much lower than that in the small intestine (39).…”
Section: Discussionmentioning
confidence: 97%
“…The mucus/glycocalyx layers presumably also provide an enzymatic barrier and/or diffusional barrier. The enzymatic degradation of insulin in the mucus/glycocalyx layers tends to increase toward the upper small intestine in the following order: duodenum>jejunum>ileum (38). By contrast, the colonic coadministration of insulin and penetratin had a smaller effect on increasing insulin absorption, even though the proteolytic activity in the colon may be much lower than that in the small intestine (39).…”
Section: Discussionmentioning
confidence: 97%
“…21,22) Hence, the effect of PLA may also be influenced by the enzymes in the mucous layer. 20) The highest F 0-4 h was obtained in the jejunum when aprotinin was co-administered with PLA. In contrast, the absorption of FD-4 was not observed to increase after the co-administering aprotinin in the colon, and the F 0-4 h was almost equal to that when only 0.5% PLA was combined with FD-4.…”
Section: Methodsmentioning
confidence: 94%
“…Meanwhile, the T max was not changed by co-administration of aprotinin in the ileum, indicating that the protease has a little influence on the enhancing effect of PLA, that is, only a little protease might exist in the ileum compared with the duodenum and jejunum. 20) The mucous layer seems to be removed incompletely in a well-established in situ closed-loop method. It has been reported that the pancreatic enzymes capable of degrading proteins resided in the mucous layer.…”
Section: Methodsmentioning
confidence: 99%
“…The calcium ion was knows as the activator of enzymatic activity related to the insulin degradation in the intestine (Yamagata et al, 2006;Madsen and Peppas, 1999). The insulin degradation is one of major barriers for the insulin permeation through the intestinal mucosa (Aoki et al, 2005), and the inhibitory effect of insulin degradation would play a crucial role for the enhancing effect of insulin absorption by the polymers.…”
Section: Discussionmentioning
confidence: 99%